The Path of Output From Plan to Market - Gylfason, Thorvaldur (IMF Working Papers; Working Paper ;, 1994)
This paper is intended to clarify the contribution of macroeconomic stabilization and structural adjustment to the transformation from plan to market in Central and Eastern Europe and elsewhere. Four main points emerge. First, increased price stability improves the utilization of capital and thus increases the level of output at full employment in the long run, even though output decreases initially. Second, the static output gain from stabilization is captured in a simple formula in which the gain is approximately proportional to the square of the original inflation distortion. Third, successful stabilization increases the rate of growth of output per head, and not only its level, in the presence of constant returns to capital in a broad sense. Fourth, substitution of plausible parameter estimates into the simple formulae reflecting the gains from stabilization indicate that the static and dynamic output gains can be quite large.